The sweet East [videorecording (Blu-Ray)] - Williams, Sean Price; Irv, Jack; Ryder, Talia; Rubin, Ella; Pinkerton, Nick (Utopia, 2023)
A picaresque journey through the cities and woods of the Eastern seaboard of the U.S undertaken by Lillian, a high school senior from South Carolina. She gets her first glimpse of the wider world on a class trip to Washington, D.C.